The Importance of Hip Hop Events and their Impact on Event Management in Dubai - Zadeh, Ali Hakim; Kleber, Daniel Marco-Stefan (KINERJA, 2019)
Background – Events and concerts give participants a chance to display their talents or showcase a new idea, perspective or invention. Dubai has established itself as one of the major destinations for events, specifically in the genre of Hip Hop. Hip Hop has become a worldwide cultural phenomenon and has impacted Dubai’s large international young community. The world market is becoming increasingly saturated and differentiation has become essential.Purpose – An assessment needs to be conducted on the usage of marketing and event management tools in major hip hop events and their effectiveness in providing economic benefit.Design/methodology/approach – This research study will utilize both primary and secondary data sources, mainly primary, in the form of interviews with industry professionals and experts in Dubai’s event field, to obtain an accurate perspective.Findings – Understanding the importance of hip hop and its economic impact will help to open up a new perspective to current research streams in the field. The research will focus on three key areas through analyzing Dubai’s hip hop events significance:- The city’s ability to differentiate itself through hip hop events.- The ability to attract major artists and audience from the region.- The benefits for the event management sector. Research limitations – At this stage, there is limited secondary data on this topic as Hip Hop events are specifically occurring in select cities with the infrastructural, audience, and economic provisions.Originality/value – Development of surrounding businesses, employment opportunities, culture awareness and crowd attraction are potential outcomes which can be expected from the above presented events in Dubai. The study aims at supporting a successful initiation and execution of hip-hop events which will give Dubai an economic edge against its competitors in this growing sector. Keywords: Culture, Dubai, Events, Event Management, Hip-Hop